Gender Identity Disorder Pada Tokoh Yuuta Aoki Dalam Komik Bokura No Hentai Karya Fumi Fumiko - Ariska Dwi Cahyani, Ni Komang Ayu (Humanis; Vol 22 No 4 (2018), 2018)
The title of this research is “Gender Identity disorder at character Yuuta Aoki in manga Bokura no Hentai by Fumi Fumiko”. The aims of this research are to described GID characteristic, the reasons of GID in character yuuta, and any efforts the character do to deal with his own GID in manga Bokura no Hentai by Fumi Fumiko. The theories that have been used are Wellek and Warren’s literature and psychology theory (2016), Sigmund Freud’spsychoanalytic theory (2016), First’s gender identity disorder theory (1994), and Marcel Danesi’s semiotic theory (2011). From the results, it is showed that character Yuuta Aoki is a boy which want to be a girl since he was 4 years old driven by his GID condition. GID characteristic in Yuuta was identified in 3 dimensions 1). Physiology, which is dress himself as a girl and use cosmetics; 2). Psychology, which is declaring himself as a girl, fall in love with boy, irritated to have a male body, imagining himself as girl, and act like a girl; 3). Sociology, which is often got bullied by his friends and usually hanging out with his female friends. The reasons behind Yuuta’s GID condition were driven by mimicking and his mother let him to dress himself as a girl. His efforts to deal with his GID were by trying to act like a boy again and consulting with doctor.